2017
DOI: 10.1188/17.onf.413-420
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Benefits and Barriers to Exercise for Recently Treated Adults With Acute Leukemia

Abstract: Purpose/Objectives To explore perceived exercise benefits and barriers in adults with acute leukemia who recently completed an inpatient exercise intervention during induction therapy. Research Approach Descriptive, exploratory design using semistructured interviews. Setting Inpatient hematology/oncology unit at North Carolina Cancer Hospital in Chapel Hill. Participants 6 adults with acute leukemia aged 35–67 years. Methodologic Approach Content analyses of semistructured interviews that were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(68 citation statements)
references
References 26 publications
4
61
0
3
Order By: Relevance
“…AL develops rapidly and can cause several clinical symptoms, including fever, fatigue, anaemia, bleeding, and infection [5]. Chemotherapy, as an effective treatment, can improve the overall survival rate of patients with AL [6]. However, the side effects of chemotherapy leads to patients with significant physical and psychological challenges, which affects their quality of life (QoL) [7].…”
Section: Introductionmentioning
confidence: 99%
“…AL develops rapidly and can cause several clinical symptoms, including fever, fatigue, anaemia, bleeding, and infection [5]. Chemotherapy, as an effective treatment, can improve the overall survival rate of patients with AL [6]. However, the side effects of chemotherapy leads to patients with significant physical and psychological challenges, which affects their quality of life (QoL) [7].…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study of patients with acute leukaemia who completed an exercise intervention during inpatient treatment found that most participants were not meeting the recommendations for physical activity of 150 min per week prior to their diagnosis, and were overall positive about the exercise intervention though barriers for participation included anxiety, aches and pains (Leak Bryant et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis of the efficacy of exercise interventions (n = 9) in patients with acute leukaemia found beneficial effects on cardiorespiratory fitness, muscle strength and functional mobility; however no significant improvements in fatigue, anxiety, depression or quality of life (Zhou et al, 2016). A qualitative study of patients with acute leukaemia who completed an exercise intervention during inpatient treatment found that most participants were not meeting the recommendations for physical activity of 150 min per week prior to their diagnosis, and were overall positive about the exercise intervention though barriers for participation included anxiety, aches and pains (Leak Bryant et al, 2017).…”
Section: Rehabilitationmentioning
confidence: 99%
“…AL develops rapidly and can cause several clinical symptoms, including fever, fatigue, anaemia, bleeding, and infection [5]. Chemotherapy, as an effective treatment, can improve the overall survival rate of patients with AL [6]. However, the side effects of chemotherapy leads to patients with signi cant physical and psychological challenges, which affects their quality of life (QoL) [7].…”
Section: Introductionmentioning
confidence: 99%